Biomimetic Mineralization of Metal Ion‐Doped Lipase into ZIF‐8 Framework for Enhanced Hydrolytic Activity in Biphasic System. Issue 38 (13th October 2022) - Lin, Jiale; Cheng, Yongfa; La, i, Oi‐Ming; Tan, Chin‐Ping; Panpipat, Worawan; Shen, Cai; Cheong, Ling‐Zhi
Abstract: Present work encapsulated metal ion dopped‐Candida rugosa lipase (CRL) into ZIF structure through biomimetic mineralization and evaluated hydrolytic activity of the immobilized lipase using a biphasic system. Magnesium ion (Mg 2+ ) doped‐CRL with high hydrolytic activity (237 % of free CRL) was successfully synthesized. Circular dichroism and fluorescence spectroscopy analysis revealed Mg 2+ doping has changed the conformation of CRL resulted in enhanced structural stability of CRL. The synthesized CRL/Mg 2+ @ZIF‐8 had a mesoporous (3.88 nm) structure with good crystallinity. Mg 2+ doping increased the catalytic activity, substrates affinity (lower Km of 0.4102 mM) and catalytic stability of immobilized CRL. Catalytic activity of CRL/Mg 2+ @ZIF‐8 (0.25±0.012 U) was two‐fold higher than that of CRL@ZIF‐8 (0.10±0.008 U). The synthesized CRL/Mg 2+ @ZIF‐8 was used in biosensing of a protox‐inhibiting herbicides (nitrofen) in fruit samples. CRL/Mg 2+ @ZIF‐8 can be used for biosensing of nitrofen with wide detection range (0‐50 μM), low detection limit (0.47 μM) and good recovery rate. Abstract : Metal ion dopped‐Candida rugosa lipase was encapsulated into ZIF structure through biomimetic mineralization, Mg 2+ doping has changed the conformation of CRL resulted in enhanced structural stability of CRL. CRL/Mg 2+ @ZIF‐8 was used in biosensing of a protox‐inhibiting herbicide in fruit samples with wide detection range, low detection limit and good recovery rate, and Catalytic activity of was two‐fold higher than that of CRL@ZIF‐8.